The Peanut Allergy Burden Study: Impact on the quality of life of patients and caregivers - Anna Nowak-Wegrzyn; Steven L. Hass; Sarah M. Donelson; Dan Robison; Ann Cameron; Martine Etschmaier; Amy Duhig; William A. McCann (World Allergy Organization Journal, 2021)
Background: Peanut allergy (PA) places significant burden on peanut-allergic individuals and their families, yet limited research in the United States has quantitatively examined the impact on peanut-allergic individuals and their families’ health-related quality of life (HRQoL). The Peanut Allergy Burden Study (PABS) aimed to quantify the impact of PA on the general and disease-specific HRQoL of children, adolescents, and adults with PA, as well as caregivers of children with PA. Methods: A cross-sectional survey design was employed to examine the real-world impact of PA in children, adolescents, and adults with PA, and caregivers of children with PA. Results: Of 153 adult patients, 102 adolescents, and 382 caregivers of peanut-allergic children (n = 382), 6.8% and 24.8% of participants indicated being dissatisfied or somewhat dissatisfied, respectively, with current approaches to avoid or prevent PA reactions. Approximately two-thirds of patients and caregivers indicated that PA interferes at least somewhat with daily living. In terms of general HRQoL, adolescents, adult patients, and caregivers indicated that mental/psychosocial health was more problematic than physical health. PA patients and caregivers indicated worse HRQoL in all domains compared to healthy samples, and worse overall HRQoL, psychosocial, emotional, and social functioning than a sample of chronically ill patients. Results from the allergy-specific HRQoL measures showed that adolescents experienced greater impairment in overall HRQoL due to PA and in allergen avoidance and dietary restriction than adults. Conclusion: PA negatively affects the general and PA-specific HRQoL of both patients and caregivers. The high emotional and psychosocial burden, in particular, demonstrates significant unmet need for patients with PA and their caregivers. Future work on treatment and preventive options to improve HRQoL for PA patients, particularly adolescents and their families, is needed.